The evidence for open and closed exocytosis as the primary release mechanism. (18th July 2016) - Ren, Lin; Mellander, Lisa J.; Keighron, Jacqueline; Cans, Ann-Sofie; Kurczy, Michael E.; Svir, Irina; Oleinick, Alexander; Amatore, Christian; Ewing, Andrew G.
Abstract: Exocytosis is the fundamental process by which cells communicate with each other. The events that lead up to the fusion of a vesicle loaded with chemical messenger with the cell membrane were the subject of a Nobel Prize in 2013. However, the processes occurring after the initial formation of a fusion pore are very much still in debate. The release of chemical messenger has traditionally been thought to occur through full distention of the vesicle membrane, hence assuming exocytosis to be all or none. In contrast to the all or none hypothesis, here we discuss the evidence that during exocytosis the vesicle-membrane pore opens to release only a portion of the transmitter content during exocytosis and then close again. This open and closed exocytosis is distinct from kiss-and-run exocytosis, in that it appears to be the main content released during regular exocytosis. The evidence for this partial release via open and closed exocytosis is presented considering primarily the quantitative evidence obtained with amperometry.